In the weeds - Borison, B. K. (Lovelight, 2023)
"A grumpy farmer and a no-nonsense social media influencer have another chance at love in this charming romantic comedy. Evelyn St. James isn't the kind of woman you forget. Beckett Porter certainly hasn't. One incredible weekend in Maine, and he's officially a man distracted. He's not unfamiliar with hot and heavy flings, but Evie wove some sort of magic over him during their tumble in the sheets. He can't stop thinking about her laugh. Her hand pressed flat against his chest. Her smiling mouth at his neck. So when she suddenly appears on his farm as part of a social media contest, he is...confused. He had no idea that the sweet and sexy woman he met at a bar is actually a global phenomenon. When Evie disappears again, Beckett resolves to finally move on. But Evie, who has been feeling disconnected from her work and increasingly dissatisfied with life online, is trying to find her way back to something real. She returns to the last place she was happy: Lovelight Farms and the tiny town of Inglewild. And it has absolutely nothing to do with the hot farmer she spent two incredible nights with"--